2021
DOI: 10.1088/1361-6501/ac15dd
|View full text |Cite
|
Sign up to set email alerts
|

Isometric contraction force measurement of hiPSC-CMs on a movable plate with a feedback-controlled MEMS cantilever probe

Abstract: We propose a measurement method with a feedback system to evaluate the contraction forces of human iPS cell-derived cardiomyocytes (hiPSC-CMs) in a dynamic mechanical environment. The measurement of the hiPSC-CM contraction forces is important for regenerative medicine; however, conventional methods are not able to evaluate these forces when the cells are subjected to a dynamic load similar to that from the heart. The proposed measurement system is composed of a micromachined piezoresistive cantilever attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, to investigate the magnitude of the displacement, it is necessary to return to the original data in Figure 5 A, and the displacement was estimated to be approximately 10 µm at 24 °C. The spring constants of the movable plate and force sensor were 2.54 N/m and 0.72 N/m, respectively, with a combined spring constant of 3.26 N/m [ 20 ]. Thus, a displacement of 10 µm corresponded to a force of approximately 33 µN.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, to investigate the magnitude of the displacement, it is necessary to return to the original data in Figure 5 A, and the displacement was estimated to be approximately 10 µm at 24 °C. The spring constants of the movable plate and force sensor were 2.54 N/m and 0.72 N/m, respectively, with a combined spring constant of 3.26 N/m [ 20 ]. Thus, a displacement of 10 µm corresponded to a force of approximately 33 µN.…”
Section: Resultsmentioning
confidence: 99%
“…We used MEMS-based cantilever force sensors to investigate how the beating frequency of hiPSC-CMs changes with temperature. The use of silicon-based force sensors for studying cellular forces has advantages in terms of temporal resolution [ 18 , 19 , 20 , 30 , 31 ]. Silicon-based force sensors have temporal resolutions in the order of GHz, and it has been reported that the force can be measured in units of adhesive spots on cells because of their high measurement speed of 400 kHz [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations